Kondisi Spritual Dengan Kualitas Hidup Lansia - Sinta Novelti Bawata; Bayu Dwisetyo; I Made Rantiasa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Poor quality of life in the elderly has the potential to cause various complications that worsen their well-being.The importance of spirituality in the lives of the elderly, which is related to old age, is associated with the limitations and difficulties in the abilities of the elderly.The purpose of this study is to determine the relationship between spiritual conditions and the quality of life of the elderly in Marinsow Village, Likupang Timur District, North Minahasa Regency.The research uses a cross-sectional design.The sample in this study consisted of 54 respondents using the purposive sampling technique.Data collection on spiritual conditions and quality of life was conducted using a questionnaire and analyzed using the chi-square statistical test.The results of the study showed that the most common level of spirituality was moderate spirituality, with 32 respondents (59.3%), and the most common quality of life was moderate quality of life, with 30 respondents (55.6%).The results of the Somers test obtained a p-value of 0.000 where < α 0.05.Conclusion: There is a relationship between spiritual condition and the quality of life of the elderly in Marinsow Village, Likupang Timur District, North Minahasa Regency.